One lung ventilation strategies for infants and children undergoing video assisted thoracoscopic surgery - Fabila, Teddy Suratos (Medknow Publications & Media Pvt Ltd, 2013)
The advantages of video assisted thoracoscopic surgery (VATS) in children have led to its increased usage over the years. VATS, however, requires an efficient technique for one lung ventilation. Today, there is an increasing interest in developing the technique for lung isolation to meet the anatomic and physiologic variations in infants and children. This article aims to provide an updated and comprehensive review on one-lung ventilation strategies for infants and children undergoing VATS. Search of terms such as ‘One lung ventilation for infants and children’, ‘Video assisted thoracoscopic surgery for infants and children’, and ‘Physiologic changes during one lung ventilation for infants and children’ were used. The search mechanics and engines for this review included the following: Kandang Kerbau Hospital (KKH) eLibrary, PubMed, Ovid Medline, Cochrane Central Register of Controlled Trials, and Cochrane Database of Systematic Reviews. During the search the author focused on significant current and pilot randomized control trials, case reports, review articles, and editorials. Critical decision making on what device to use based on the age, weight, and pathology of the patient; and how to use it for lung isolation are discussed in this article. Furthermore, additional information regarding the advantages, limitations, techniques of insertion and maintenance of each device for one lung ventilation in infants and children were the highlights in this article.